2022
DOI: 10.48550/arxiv.2201.06188
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relating an entanglement measure with statistical correlators for two-qudit mixed states using only a pair of complementary observables

Abstract: We focus on characterizing entanglement of high dimensional bipartite states using various statistical correlators for two-qudit mixed states. The salient results obtained are as follows: (a) A scheme for determining the entanglement measure given by Negativity is explored by analytically relating it to the widely used statistical correlators viz. mutual predictability, mutual information and Pearson Correlation coefficient for different types of bipartite arbitrary dimensional mixed states. Importantly, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However, Maccone et al justified this conjecture only by showing its applicability for bipartite qubits and the validity of this conjecture has remained uninvestigated for dimensions d > 2. In this work, we justify the validity of this conjecture for pure bipartite qutrits by deriving an analytic relation between PCC and N for any arbitrary dimension d (details of this derivation are provided in a separate paper [22]), and this relation is tested by applying it to quantify the amount of entanglement in our experimentally generated pure bipartite qutrits (d = 3). PCC for a joint observable X A ⊗ X B is given by equation ( 3) where the observable, X can be written as X = i,j: i|j =0 |j i| and is such that it projects each computational basis |i to the superposition of all the remaining basis vectors of the complete set.…”
Section: Deriving An Analytic Relation Between Pcc and N For Pure Bip...mentioning
confidence: 95%
See 2 more Smart Citations
“…However, Maccone et al justified this conjecture only by showing its applicability for bipartite qubits and the validity of this conjecture has remained uninvestigated for dimensions d > 2. In this work, we justify the validity of this conjecture for pure bipartite qutrits by deriving an analytic relation between PCC and N for any arbitrary dimension d (details of this derivation are provided in a separate paper [22]), and this relation is tested by applying it to quantify the amount of entanglement in our experimentally generated pure bipartite qutrits (d = 3). PCC for a joint observable X A ⊗ X B is given by equation ( 3) where the observable, X can be written as X = i,j: i|j =0 |j i| and is such that it projects each computational basis |i to the superposition of all the remaining basis vectors of the complete set.…”
Section: Deriving An Analytic Relation Between Pcc and N For Pure Bip...mentioning
confidence: 95%
“…for the state, ψ AB as given by the equation ( 4). Furthermore, it can be shown that as discussed in [22],…”
Section: Deriving An Analytic Relation Between Pcc and N For Pure Bip...mentioning
confidence: 96%
See 1 more Smart Citation
“…Knowledge of the precise noise present in our experiment can lead to stronger entanglement criteria 85,86 , but since we do not know the relevant noise, we adopt an approach where the state is treated as uncharacterized. In our analysis, we assume that Alice's measurements correspond to the computational basis and the first MUB, respectively.…”
Section: High-dimensional Entanglement Certification With Systematic ...mentioning
confidence: 99%